Simple surgical technique for epicardial pacemaker wire preparation and insertion - Amit Mishra; Kartik Patel; Chandrasekaran Ananthanarayananh; Vivek Wadhawa; Himani Pandya (Journal of the Practice of Cardiovascular Sciences, 2022)
Epicardial pacing wire (EPW) insertion is an integral part of open heart surgery. However, the use of EPW insertion is also associated with complications such as bleeding, tamponade, arrhythmias, and occasionally even death of the patient. Various techniques have been described for preparing, placing, and removing EPW. We present our simple, yet effective technique of preparing, inserting, and removing EPW where the incidence of complications is nil.